Layered double hydroxides loaded sludge biochar composite for adsorptive removal of benzotriazole and Pb(II) from aqueous solution. (January 2022) - Cheng, Xiaojuan; Deng, Jiaqin; Li, Xiaodong; Wei, Xue; Shao, Yanan; Zhao, Yanlan
Abstract: In this work, a novel sludge biochar/Zn–Al layered double hydroxide composite (SL) was synthesized in a facile co-precipitation method, and it was used to simultaneously remove benzotriazole (BTA) and lead ion (Pb(II)). Batch adsorption experiments demonstrated that composites with sludge content of 1.0 g (SL-1.0) had a great adsorption performance for BTA and Pb(II). The maximum adsorption capacities of SL-1.0 for BTA and Pb(II) were 239.6 and 226.1 mg g −1, respectively. There was preferential adsorption of BTA in BTA and Pb(II) binary system. The adsorption mechanism analysis indicated that the BTA and Pb(II) adsorption involved electrostatic attraction and chemical bonding with surface functional groups on SL-1.0. Specifically, hydrogen bonding and π-π interaction were mainly ascribed to BTA adsorption, while complexation with surface function groups dominated Pb(II) adsorption. With the advantages of facile synthesis and excellent adsorption capacity, SL-1.0 possesses great potential for simultaneously removing of BTA and Pb(II) from wastewaters. Graphical abstract: Image 1 Highlights: A novel adsorbent (SL-1.0) was successfully prepared by loading LDH onto SBC. The existence of benzotriazole had little effect on Pb(II) adsorption onto SL-1.0. There was preferential adsorption of benzotriazole in the binary system of benzotriazole and Pb(II). Hydrogen bonding and π-π interaction were mainly ascribed to benzotriazole adsorption. The complexation with surface function groups dominated Pb(II) adsorption.